Navigating communication paradigms in the digital age: a comparative review / Diah Ayu Permatasari, Istianingsih, M. Yusuf Samad and Oswald Timothy Edward - -, Diah Ayu Permatasari; -, Istianingsih; Samad, M. Yusuf; Edward, Oswald Timothy (UiTM Cawangan Johor, 2024)
This literature review aims to comprehensively explore the impact of social media on communication paradigms and societal structures in the digital age. The review adopts a qualitative approach, analyzing existing literature to understand the multifaceted implications of social media on various aspects of life and society. Social media platforms, rooted in Web 2.0, have transformed communication by enabling the creation and exchange of user-generated content. The functional building blocks of social media, including sharing, presence, relationships, identity, conversations, and reputation, play a critical role in shaping information dissemination and perception. The rapid adoption of social media has significantly impacted industries such as public relations, journalism, and marketing, necessitating adaptive strategies to address real-time communication demands. The findings of this review have practical implications for policymakers, educators, businesses, and society as a whole. They emphasize the importance of responsible and strategic use of social media in the digital age.